Determinan kemiskinan di Provinsi Jawa Timur: peran pertumbuhan penduduk, indeks pembangunan manusia, dan tingkat pengangguran terbuka - Silvia Usmayanti Putri; Husna Qonita; Lailatul Fadilah; Agus Eko Sujianto (Nur Science Institute, 2026)
This study aims to analyze the effects of population growth rate, human development index, and open unemployment rate on poverty levels in East Java Province for the period 2020-2024. The issue of poverty, which remains a development challenge, underscores the need for an analysis of the factors influencing it, both in terms of demographics and the quality of human resources. This study employs a quantitative approach using panel data regression analysis that combines temporal and spatial dimensions at the district/city level. The results indicate that the human development index has a negative and significant effect on poverty rates, meaning that improvements in human capital can reduce poverty. Meanwhile, population growth rates and open unemployment rates show a positive but insignificant effect on poverty rates. Collectively, these three variables influence poverty levels. Thus, this study concludes that improving the quality of human development is a key factor in efforts to reduce poverty in East Java, whereas demographic factors and unemployment have relatively limited effects.